2020
DOI: 10.1186/s13071-020-04386-7
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature tolerance of three Aedes albopictus strains (Diptera: Culicidae) under constant and fluctuating temperature scenarios

Abstract: Background Aedes albopictus, a vector of numerous viruses and filarial worms, has already established in 20 countries in Europe, mainly colonising subtropical regions. Continuing adaptation to climatic conditions in temperate areas would probably result in a spread to more northern European countries, producing an increasing risk of mosquito-borne pathogen transmission over a much greater area. Based on previous studies showing that Ae. albopictus is able to overwinter in Germany, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
2
16
0
1
Order By: Relevance
“…albopictus strains originating from tropic regions, which are less tolerant to cooler climate compared with strains from temperate regions [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…albopictus strains originating from tropic regions, which are less tolerant to cooler climate compared with strains from temperate regions [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…albopictus incidence due to optimal conditions for larval rearing with warmer temperatures [ 9 , 50 , 70 ], although Ae. albopictus are also resistant to low temperatures [ 9 , 71 ]. In our study, we found that precipitation was the main environmental factor influencing adult Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe Waldock et al (2013) suggested to use a -4°C isotherm, while in the USA a threshold of -5°C was suggested (Khan et al, 2020). Tippelt et al (2020) specify that the vector is capable of overwintering at temperatures <2°C in Europe.…”
Section: Climatic Thresholdsmentioning
confidence: 99%